Optimalisasi Keuntungan Penjualan Produk UMKM ‘Batagor Bandung Tarakan’ Dengan Metode Simpleks dan POM-QM - Hidayat, Nurul; Mardiah, Aenun; Amran, Arini; Vebriansyah, Vebriansyah (FEB Universitas Maritim Semarang, 2025)
This study aims to optimize sales profit at the MSME Batagor Bandung Tarakan by applying the Simplex method in linear programming, supported by the POM-QM for Windows software. Profit optimization plays a crucial role in strategic decision-making, particularly in determining the optimal daily production quantities to enhance operational efficiency, maximize the use of raw materials, and meet market demand effectively. The Simplex method was chosen for its ability to solve linear optimization problems involving multiple constraints and variables, providing accurate mathematical solutions to achieve maximum profit. This research utilizes daily production data as the basis for analysis, which is then processed using the Simplex method in POM-QM. The results show that implementing the Simplex method can increase daily profits from IDR 634,000 to IDR 831,408 through a more efficient production combination. The study concludes that the Simplex method, when applied via the POM-QM software, is an effective tool for daily production decision-making and can support MSMEs like Batagor Bandung Tarakan in improving their competitiveness and business sustainability.